All-solid-state lithium-ion battery and preparation method thereof

By neatly stacking battery components in all-solid-state lithium-ion batteries and introducing microporous structures and lithium supplements, the problems of layering and cracking in battery manufacturing are solved, and the uniformity, bonding and cycling performance of the battery are improved.

CN119764528APending Publication Date: 2025-04-04FARASIS TECH (GANZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411958573.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the existing battery manufacturing process, the wet process uses toxic solvents, which leads to electrode layering and cracks, reducing battery performance; while the dry process has challenges in bonding and uniformity, affecting the overall performance of the battery.

Method used

The design of an all-solid-state lithium-ion battery is adopted, and the conductive agent layer, the positive electrode material layer, the solid electrolyte layer, the negative electrode material layer and the current collector layer are neatly arranged, and lithium supplementation agent is introduced through the microporous structure to enhance adhesion performance and uniformity.

Benefits of technology

It improves the uniformity and consistency of the battery, enhances the bonding performance of the solid-state interface, solves the problem of volume expansion during the charging process, and compensates for the loss of active lithium by supplementing lithium agents, improving the cycling performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764528A_ABST
    Figure CN119764528A_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of secondary batteries, and specifically relates to an all-solid-state lithium-ion battery and a preparation method thereof. The all-solid-state lithium-ion battery comprises a composite film layer and a current collector layer located on the upper and lower sides of the composite film layer, and the composite film layer comprises a conductive agent layer, a positive electrode material layer, a solid electrolyte layer, a negative electrode material layer and a conductive agent layer from bottom to top, and a microporous structure that penetrates the positive electrode material layer, the solid electrolyte layer and the negative electrode material layer; the composite film layer is folded in a Z shape, and the microporous structure is filled with a lithium supplement. The conductive agent layer, the positive electrode material layer, the solid electrolyte layer, the negative electrode material layer and the current collector layer are neatly stacked and arranged, and the lithium supplement is introduced through the microporous structure to obtain an all-solid-state lithium-ion battery with excellent comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to an all-solid-state lithium-ion battery and a preparation method thereof. Background Art

[0002] The traditional wet process in the preparation of electrode materials is to mix the active material, conductive agent and adhesive in a solvent in proportion, and apply it to the surface of the current collector through a coating die and roll it. The solvent used is mainly N-methylpyrrolidone (NMP), which is a toxic solvent that must be carefully recovered, purified and reused, requiring a huge, expensive and complex electrode coating machine. In addition, during the evaporation of the solvent, the binder and conductive agent of the electrode obtained by the wet process will float with the solvent and concentrate near the electrode surface, and the active material will precipitate, resulting in stratification inside the electrode, which will damage the construction of the 3D conductive network in the electrode and reduce the bonding strength between the active material and the current collector. During the evaporation of the solvent, the electrode is also prone to cracks, especially thick electrodes, resulting in the thickness of the electrode being limited by the wet coating manufacturing process.

[0003] The dry process is to roll the electrode material directly onto the metal current collector to form a finished electrode. There is no need to add organic solvents, which avoids the side reactions of organic solvents during the electrochemical reaction and the consumption of active substances. The process is simple and the electrode thickness is controllable, which can reduce production costs, increase the loading amount of active substances, and improve battery performance at a lower cost. However, the dry method of preparing electrodes makes it more difficult to bond between the components, and the electrode materials are easy to peel off after multiple cycles; the internal impedance of the electrode also increases, and there may be battery polarization problems under high current; the uniformity and consistency of the film formation are more difficult to control, and the requirements for the rolling process are also higher. The electrodes of electric vehicle batteries are larger and thicker than those of supercapacitors, and the production difficulty is also higher. Summary of the invention

[0004] The purpose of the present invention is to solve the above-mentioned technical problems and provide an all-solid-state lithium-ion battery, in which the conductive agent layer, the positive electrode material layer, the solid electrolyte layer, the negative electrode material layer and the current collector layer are neatly stacked and arranged, which can enhance the uniformity and consistency of the all-solid-state lithium-ion battery, improve the bonding performance of the solid-solid interface, and introduce a lithium supplement through a microporous structure, thereby improving the overall performance of the battery.

[0005] The all-solid-state lithium-ion battery in the technical solution of the present invention comprises a composite membrane layer and current collector layers located on the upper and lower sides of the composite membrane layer, wherein the composite membrane layer comprises, from bottom to top, a conductive agent layer, a positive electrode material layer, a solid electrolyte layer, a negative electrode material layer and a conductive agent layer, as well as a microporous structure that penetrates the positive electrode material layer, the solid electrolyte layer and the negative electrode material layer.

[0006] Furthermore, the thickness of the current collector layer is 5 to 30 μm, preferably 6 to 10 μm.

[0007] The current collector in the present invention is not limited, and any current collector that can be used for lithium-ion batteries can be used. The current collector can be any one of aluminum foil, copper foil, stainless steel sheet, nickel sheet, titanium sheet, and carbon-coated sheet.

[0008] Furthermore, the thickness of the single conductive agent layer and the solid electrolyte layer in the composite film layer is 1-10 μm; and / or the thickness of the positive electrode material layer and the negative electrode material layer in the composite film layer is 1-20 μm.

[0009] Furthermore, the conductive agent layer is obtained by hot pressing after mixing the conductive agent and the binder in a mass ratio of 50 to 99:1 to 50; and / or the positive electrode material layer is obtained by hot pressing after mixing the positive electrode active material and the binder in a mass ratio of 70 to 99:1 to 30; and / or the solid electrolyte layer is obtained by hot pressing after mixing the solid electrolyte and the binder in a mass ratio of 70 to 99:1 to 30; and / or the negative electrode material layer is obtained by hot pressing after mixing the negative electrode active material and the binder in a mass ratio of 70 to 99%:1 to 30%.

[0010] Preferably, the mass ratio of the conductive agent to the binder in the conductive agent layer is 50-80:20-50; the mass ratio of the positive electrode active material to the binder in the positive electrode material layer is 85-98:2-15; the mass ratio of the solid electrolyte to the binder in the solid electrolyte layer is 80-98:1-20; the mass ratio of the negative electrode active material to the binder in the negative electrode material layer is 80-98:1-20.

[0011] The conductive agent in the present invention is not limited, and any conductive agent that can be used in lithium-ion batteries can be used. The conductive agent can be listed as one or more of conductive graphite, conductive carbon black, conductive nano-carbon fiber, carbon nanotube, and graphene.

[0012] The positive electrode active material in the present invention is not limited, and any positive electrode active material that can be used for lithium-ion batteries can be used. The positive electrode active material can be listed as one or more of lithium-rich manganese, lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, and lithium iron manganese phosphate.

[0013] Furthermore, the solid electrolyte is one or more of a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte, and a halide solid electrolyte.

[0014] Preferably, sulfide solid electrolytes can be listed as LiPSCl, LiGePS, and LiPS; oxide solid electrolytes can be listed as LATP, LZSP, LLPO, and LLZO; polymer solid electrolytes can be listed as PEO, PAN, and PMMA; and halide solid electrolytes can be listed as LiZrCl, LiInCl, and LiYBr.

[0015] The negative electrode material in the present invention is not limited, and any negative electrode material that can be used for lithium-ion batteries can be used. The negative electrode material can be one or more of graphite, silicon, silicon oxide, silicon carbon, lithium titanate, hard carbon, soft carbon, and titanium dioxide.

[0016] Furthermore, the diameter of the microporous structure is 1 to 20 μm.

[0017] Furthermore, the microporous structure is filled with a lithium supplement until the pores are completely filled.

[0018] Furthermore, the lithium supplement is one or more of lithium nickel oxide, lithium iron oxide, lithium manganese oxide, lithium cobalt oxide, and lithium rhenium oxide.

[0019] The binder in the present invention is not limited, and any binder that can be used for solid batteries can be used. The binder can be one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyacrylic acid, carboxymethyl cellulose, polyacrylonitrile, polyvinyl acid, polyamide, and polyacrylamide.

[0020] Furthermore, the composite film layer is folded in a Z shape.

[0021] When folded in a Z shape, the two ends of the composite film layer in the length direction can be marked as the first end and the second end, the first end is fixed, and the second end is folded toward the first end and the second end in sequence, and back and forth, and the area of ​​the film layer obtained each time is the same.

[0022] Furthermore, the composite film layer is folded in a Z-shape 1 to 10 times, preferably 3 to 6 times, and excess material at the edge is cut off.

[0023] The present invention also provides a method for preparing the above-mentioned all-solid-state lithium-ion battery, comprising the following steps:

[0024] (1) stacking a positive electrode material layer, a solid electrolyte layer, and a negative electrode material layer, and hot pressing to obtain a first membrane;

[0025] (2) punching holes in the first diaphragm;

[0026] (3) stacking conductive agent layers on the upper and lower sides of the first film, and hot pressing to obtain a composite film layer;

[0027] (4) stacking current collector layers on the upper and lower sides of the composite membrane layer, and finally performing hot pressing.

[0028] The present invention adopts a dry process, first separately prepares a conductive agent layer, a positive electrode material layer, a solid electrolyte layer and a negative electrode material layer, then neatly stacks and arranges the positive electrode material layer, the solid electrolyte layer and the negative electrode material layer, punches the composite layer after hot pressing, and fills the lithium supplement, stacks the conductive agent layer and hot presses to obtain a composite film layer, folds it in a Z shape, and finally stacks the current collector layer to form an all-solid-state lithium-ion battery. A binder is added during the preparation of the conductive agent layer, the positive electrode material layer, the solid electrolyte layer and the negative electrode material layer, which can effectively enhance the uniformity and consistency between the battery components, improve the bonding performance of the solid-solid interface, solve the solid-solid interface problem, and improve the overall performance of the battery.

[0029] Furthermore, in step (2), the first membrane is perforated, and a lithium supplement is added into the obtained microporous structure.

[0030] The present invention replenishes lithium through a microporous structure. On the one hand, the microporous structure reserves expansion space during the battery charging process to solve the problem of volume expansion of the battery during the charging process, which causes performance degradation, so that the battery can work normally under a small external pressure. On the other hand, adding a lithium replenisher to the microporous structure can effectively compensate for the irreversible loss of active lithium, ensure the sufficiency of active lithium in the battery, and improve the battery's cycle performance.

[0031] Furthermore, the area of ​​the microporous structure is 1.0-20.0% of the area of ​​the first membrane; preferably, the area of ​​the microporous structure is 2.0-10.0% of the area of ​​the first membrane. When the area of ​​the microporous structure accounts for too little, it is not conducive to constructing a high-speed lithium ion transmission channel. When the area of ​​the microporous structure accounts for too much, it will cause loss of active materials and reduce the energy density of the battery.

[0032] Preferably, the composite membrane layer is cut before the current collector layers are stacked on the upper and lower sides.

[0033] Furthermore, in step (4), the composite film layer is folded in a Z shape, and then current collector layers are stacked on the upper and lower sides thereof, and finally hot pressing is performed.

[0034] Furthermore, during hot pressing, the temperature is 60-150° C., the pressure is 0.1-5.0 tons (the unit of the equipment is tons, multiplied by the gravity acceleration of 9.8, which is kN), and the time is 0.1-3.0 minutes.

[0035] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0036] (1) The present invention neatly stacks and arranges the conductive agent layer, the positive electrode material layer, the solid electrolyte layer, the negative electrode material layer and the current collector layer, and introduces a lithium supplement through a microporous structure to obtain an all-solid-state lithium-ion battery with excellent comprehensive performance;

[0037] (2) Adding binders during the preparation of the conductive agent layer, positive electrode material layer, solid electrolyte layer and negative electrode material layer can effectively enhance the uniformity and consistency between battery components, improve the bonding performance of the solid-solid interface, solve the solid-solid interface problem, and improve the overall performance of the battery;

[0038] (3) The microporous structure reserves expansion space during the battery charging process, which can solve the problem of volume expansion and performance degradation during the charging process, so that the battery can work normally under a small external pressure;

[0039] (4) Adding lithium supplements to the microporous structure can effectively compensate for the irreversible loss of active lithium, ensure sufficient active lithium in the battery, and improve the battery's cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 Schematic diagram of the all-solid-state lithium-ion battery obtained in Example 1;

[0041] Figure 2 This is a schematic diagram of the all-solid-state lithium-ion battery obtained in Comparative Example 4;. DETAILED DESCRIPTION

[0042] The technical scheme of the present invention is further described below by specific examples and accompanying drawings. It should be understood that the specific examples described herein are only used to help understand the present invention and are not intended for specific limitations of the present invention. The accompanying drawings used herein are only for better illustrating the disclosure of the present invention and do not have a limiting effect on the scope of protection. If not otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.

[0043] Example 1

[0044] The method for preparing the all-solid-state lithium-ion battery of this embodiment comprises the following steps:

[0045] (1) mixing nickel cobalt manganese oxide Ni95 (Ni:CO:Mn molar ratio is 95:4:1) and polytetrafluoroethylene in a mass ratio of 95:5, and hot pressing at 80° C. and 1.0 ton pressure for 2.0 min to obtain a positive electrode material layer with a thickness of 10 μm;

[0046] (2) Conductive carbon black Super P and polytetrafluoroethylene were mixed uniformly in a mass ratio of 50:50, and hot pressed at 80° C. and 1.0 ton pressure for 1.0 min to obtain a conductive agent layer with a thickness of 2 μm;

[0047] (3) Graphite and silicon carbon (graphite: silicon carbon = 60:40) and polytetrafluoroethylene were mixed uniformly in a mass ratio of 95:5, and hot pressed at 80° C. and 1.0 ton pressure for 2.0 min to obtain a negative electrode material layer with a thickness of 10 μm;

[0048] (4) mixing lithium sulfide solid electrolyte LiPSCl and polytetrafluoroethylene in a mass ratio of 95:5, and hot pressing at 80° C. and 1.0 ton pressure for 1.0 min to obtain a solid electrolyte layer with a thickness of 4 μm;

[0049] (5) stacking the positive electrode material layer, the solid electrolyte layer and the negative electrode material layer in order, and hot pressing them at 80° C. and 1.0 ton pressure for 3.0 min to obtain a first membrane;

[0050] (6) punching holes in the first membrane, the pore size of the obtained micropores is 10 μm, the area of ​​the micropore structure is 3.0% of the area of ​​the first membrane, and nickel oxide lithium is added into the pores;

[0051] (7) stacking conductive agent layers on the upper and lower sides of the first membrane, and hot pressing at 80° C. and 1.0 ton pressure for 2.0 min to obtain a composite membrane layer;

[0052] (8) The composite film layer was folded four times in a Z-shape, cut to 70×255 mm, and then a copper foil with a thickness of 6 μm was stacked on the upper and lower sides thereof. Finally, the composite film layer was hot-pressed at 80°C and a pressure of 1.0 ton for 3.0 min. The obtained all-solid-state lithium-ion battery was as follows Figure 1 shown.

[0053] Example 2

[0054] The method for preparing the all-solid-state lithium-ion battery of this embodiment comprises the following steps:

[0055] (1) lithium cobalt oxide and polytetrafluoroethylene were mixed uniformly in a mass ratio of 90:10, and hot pressed at 80° C. and 1.0 ton pressure for 2.0 min to obtain a positive electrode material layer with a thickness of 5 μm;

[0056] (2) mixing graphene and polytetrafluoroethylene in a mass ratio of 60:40, and hot pressing at 80° C. and 1.0 ton pressure for 2.0 min to obtain a conductive agent layer with a thickness of 4 μm;

[0057] (3) Graphite and silicon carbon (graphite: silicon carbon = 60:40) and polytetrafluoroethylene were mixed uniformly in a mass ratio of 95:5, and hot pressed at 80° C. and 1.0 ton pressure for 2.0 min to obtain a negative electrode material layer with a thickness of 5 μm;

[0058] (4) mixing the oxide solid electrolyte LLTO and polytetrafluoroethylene in a mass ratio of 80:20, and hot pressing for 2.0 min at 80° C. and 1.0 ton pressure to obtain a solid electrolyte layer with a thickness of 2 μm;

[0059] (5) stacking a positive electrode material layer, a solid electrolyte layer, and a negative electrode material layer in this order, and hot pressing to obtain a first membrane;

[0060] (6) punching holes in the first membrane, the pore size of the obtained micropores is 8 μm, the area of ​​the micropore structure is 4.0% of the area of ​​the first membrane, and nickel oxide lithium is added into the pores;

[0061] (7) stacking conductive agent layers on the upper and lower sides of the first membrane, and hot pressing at 85° C. and 1.0 ton pressure for 3.0 min to obtain a composite membrane layer;

[0062] (8) The composite film layer was folded three times in a Z-shape, cut to 70×255 mm, and then a copper foil with a thickness of 6 μm was stacked on the upper and lower sides thereof, and finally hot-pressed at 85° C. and a pressure of 1.0 ton for 5.0 min.

[0063] Example 3

[0064] The method for preparing the all-solid-state lithium-ion battery of this embodiment comprises the following steps:

[0065] (1) nickel cobalt manganese oxide Ni95 (Ni:CO:Mn three elements molar ratio is 95:4:1) and polytetrafluoroethylene are mixed in a mass ratio of 95:5, and hot pressed at 80° C. and 1.0 ton pressure for 5.0 min to obtain a positive electrode material layer with a thickness of 15 μm;

[0066] (2) Conductive carbon black Super P and polytetrafluoroethylene were mixed uniformly in a mass ratio of 70:30, and hot pressed at 80° C. and 1.0 ton pressure for 2.0 min to obtain a conductive agent layer with a thickness of 5 μm;

[0067] (3) mixing silicon oxide and polytetrafluoroethylene in a mass ratio of 80:20, and hot pressing at 80° C. and 1.0 ton pressure for 5.0 min to obtain a negative electrode material layer with a thickness of 15 μm;

[0068] (4) mixing polymer solid electrolyte PEO and polytetrafluoroethylene in a mass ratio of 90:10, and hot pressing at 80° C. and 1.0 ton pressure for 2.0 min to obtain a solid electrolyte layer with a thickness of 5 μm;

[0069] (5) stacking the positive electrode material layer, the solid electrolyte layer and the negative electrode material layer in order, and hot pressing them at 80° C. and 1.0 ton pressure for 2.0 min to obtain a first membrane;

[0070] (6) punching holes in the first membrane, the pore size of the obtained micropores is 6 μm, the area of ​​the micropore structure is 5.0% of the area of ​​the first membrane, and lithium manganese oxide is added into the pores;

[0071] (7) stacking conductive agent layers on the upper and lower sides of the first membrane, and hot pressing at 80° C. and 1.0 ton pressure for 3.0 min to obtain a composite membrane layer;

[0072] (8) The composite film layer was folded three times in a Z-shape, cut to 70×255 mm, and then 6 μm thick aluminum foil was stacked on the upper and lower sides thereof, and finally hot pressed at 80° C. and 1.0 ton pressure for 5.0 min.

[0073] Example 4

[0074] The difference between this embodiment and embodiment 1 is that in step (8), the composite film layer is folded six times in a Z-shape, cut to 70×255 mm, and then 6 μm thick copper foil is stacked on the upper and lower sides thereof, and finally hot pressed at 80° C. and 1.0 ton pressure for 3.0 min.

[0075] Example 5

[0076] The difference between this embodiment and embodiment 1 is that in step (8), the composite film layer is folded once in a Z shape, cut to 70×255 mm, and then copper foil with a thickness of 6 μm is stacked on the upper and lower sides thereof, and finally hot pressed at 80° C. and 1.0 ton pressure for 3.0 min.

[0077] Example 6

[0078] The difference between this embodiment and embodiment 1 is that in step (8), the composite film layer is folded ten times in a Z-shape, cut to 70×255 mm, and then copper foil with a thickness of 6 μm is stacked on its upper and lower sides, and finally hot-pressed at 80° C. and 1.0 ton pressure for 3.0 min.

[0079] Example 7

[0080] The difference between this embodiment and embodiment 1 is that in step (6), the first membrane is perforated, the pore size of the obtained micropores is 10 μm, the area of ​​the micropore structure is 1.0% of the area of ​​the first membrane, and nickel oxide lithium is added into the pores.

[0081] Example 8

[0082] The difference between this embodiment and embodiment 1 is that in step (6), the first membrane is perforated, the pore size of the obtained micropores is 10 μm, the area of ​​the micropore structure is 12.0% of the area of ​​the first membrane, and nickel oxide lithium is added into the pores.

[0083] Comparative Example 1

[0084] The preparation method of the all-solid-state lithium-ion battery of this comparative example comprises the following steps:

[0085] (1) nickel cobalt manganese oxide Ni95 (Ni:CO:Mn molar ratio is 95:4:1) is mixed with polytetrafluoroethylene and conductive carbon black Super P in a mass ratio of 90:5:5, and hot pressed at 80°C and 1.0 ton pressure for 2.0 min to obtain a positive electrode material layer with a thickness of 10 μm;

[0086] (2) Graphite and silicon carbon (graphite: silicon carbon = 60:40) were mixed with polytetrafluoroethylene and conductive carbon black Super P in a mass ratio of 90:5:5, and hot pressed at 80° C. and 1.0 ton pressure for 2.0 min to obtain a negative electrode material layer with a thickness of 10 μm;

[0087] (3) mixing lithium sulfide solid electrolyte LiPSCl and polytetrafluoroethylene in a mass ratio of 95:5, and hot pressing at 80° C. and 1.0 ton pressure for 2.0 min to obtain a solid electrolyte layer with a thickness of 4 μm;

[0088] (4) stacking the positive electrode active layer, the solid electrolyte layer and the negative electrode material layer in order, and hot pressing them at 80° C. and 1.0 ton pressure for 2.0 min to obtain a first membrane;

[0089] (5) punching holes in the first membrane, the pore size of the obtained micropores is 10 μm, the area of ​​the micropore structure is 3.0% of the area of ​​the first membrane, and adding nickel oxide lithium into the pores to obtain a composite membrane layer;

[0090] (6) The composite film layer was folded four times in a Z shape, cut to 70×255 mm, and then a 6 μm thick copper foil was stacked on the upper and lower sides of the composite film layer. Finally, it was hot pressed at 80° C. and 1.0 ton pressure for 2.0 min.

[0091] Comparative Example 2

[0092] The difference between this comparative example and Example 1 is that in step (6), after the composite film layer is cut into 70×255 mm, copper foils with a thickness of 6 μm are stacked on the upper and lower sides thereof, and finally hot-pressed at 80° C. and 1.0 ton pressure for 2.0 min.

[0093] Comparative Example 3

[0094] The difference between this comparative example and Example 1 is that step (6) is to punch holes in the first membrane sheet, the pore size of the obtained micropores is 10 μm, and the area of ​​the micropore structure is 3.0% of the area of ​​the first membrane sheet.

[0095] Comparative Example 4

[0096] The difference between this comparative example and Example 1 is that step (8) is to cut the composite film layer into 70×255 mm, stack copper foils with a thickness of 6 μm on the upper and lower sides thereof, and finally perform hot pressing. The obtained all-solid-state lithium-ion battery is as follows Figure 2 shown.

[0097] The all-solid-state lithium-ion batteries obtained in the above embodiments and comparative examples were welded with pole ears and packaged, and assembled into soft-pack cells for cycle performance testing. The test results are shown in Table 1.

[0098] Table 1 All-solid-state lithium-ion battery performance data table

[0099]

[0100]

[0101] In Examples 1-4, the conductive agent layer, the positive electrode material layer, the solid electrolyte layer, the negative electrode material layer and the current collector layer are neatly stacked and arranged, and a lithium replenisher is introduced through a microporous structure to obtain an all-solid-state lithium-ion battery with excellent comprehensive performance; in Example 5, the composite film layer is folded once in a Z shape, and the battery energy density is reduced; in Example 6, the composite film layer is folded ten times in a Z shape, and the internal resistance of the battery is increased, which affects the stability of the battery structure and the performance of the capacity; in Example 7, when the area ratio of the microporous structure is too small, it is not conducive to the construction of a high-speed lithium ion transmission channel, and the lithium ion transmission rate is slowed down. At the same time, the content of the lithium replenisher is small, the lithium replenishment effect is reduced, and the electrochemical performance of the battery is reduced; in Example 8, the area ratio of the microporous structure is too large, the stability of the lithium ion battery structure is reduced, and it is easy to cause the loss of active substances, thereby reducing the energy density of the battery; In Comparative Example 1, the conductive binder is mixed with the positive electrode active material, the negative electrode active material and the solid electrolyte to obtain the positive electrode material layer, the negative electrode material layer and the solid electrolyte layer. The components are unevenly dispersed to a certain extent, the consistency of the membrane is reduced, the destructive effect on the structure after folding is increased, and the electrochemical performance is worse; in Comparative Example 2, the conductive binder is mixed with the positive electrode active material, the negative electrode active material and the solid electrolyte to obtain the positive electrode material layer, the negative electrode material layer and the solid electrolyte layer. The components are unevenly dispersed to a certain extent, and the membrane interface is easily deformed, and the electrochemical performance is worse; in Comparative Example 3, the lithium replenisher is not filled after punching, and the loss of active lithium cannot be compensated, and the energy density of the obtained lithium ion battery is significantly reduced; in Comparative Example 4, the composite membrane layer is not folded, and the first coulomb efficiency and energy density of the lithium ion battery are reduced.

[0102] Finally, it should be noted that the specific embodiments described herein are merely examples of the spirit of the present invention, and are not intended to limit the implementation methods of the present invention. Those skilled in the art of the present invention may make various modifications or supplements to the described embodiments or replace them in similar ways. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.

Claims

1. An all-solid-state lithium-ion battery, characterized in that: It includes a composite membrane layer and current collector layers located on the upper and lower sides of the composite membrane layer. The composite membrane layer includes, from bottom to top, a conductive agent layer, a positive electrode material layer, a solid electrolyte layer, a negative electrode material layer and a conductive agent layer, as well as a microporous structure that penetrates the positive electrode material layer, the solid electrolyte layer and the negative electrode material layer.

2. The all-solid-state lithium-ion battery according to claim 1, characterized in that: The thickness of the single conductive agent layer and the solid electrolyte layer in the composite film layer is 1-10 μm; and / or the thickness of the positive electrode material layer and the negative electrode material layer in the composite film layer is 1-20 μm.

3. The all-solid-state lithium-ion battery according to claim 1 or 2, characterized in that: The conductive agent layer is obtained by mixing a conductive agent and a binder in a mass ratio of 50 to 99:1 to 50 and then hot pressing; And / or the positive electrode material layer is obtained by mixing the positive electrode active material and the binder in a mass ratio of 70 to 99:1 to 30 and then hot pressing; And / or the solid electrolyte layer is obtained by mixing a solid electrolyte and a binder in a mass ratio of 70 to 99:1 to 30 and then hot pressing; And / or the negative electrode material layer is obtained by mixing the negative electrode active material and the binder in a mass ratio of 70 to 99:1 to 30 and then hot pressing.

4. The all-solid-state lithium-ion battery according to claim 1, characterized in that: The diameter of the microporous structure is 1 to 20 μm.

5. The all-solid-state lithium-ion battery according to claim 1, characterized in that: The microporous structure is filled with a lithium supplement agent.

6. The all-solid-state lithium-ion battery according to claim 1, characterized in that: The composite film layer is folded in a Z shape.

7. The all-solid-state lithium-ion battery according to claim 6, characterized in that: The composite film layer is folded in a Z-shape 1 to 10 times.

8. A method for preparing an all-solid-state lithium-ion battery according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) stacking a positive electrode material layer, a solid electrolyte layer, and a negative electrode material layer, and hot pressing to obtain a first membrane; (2) punching holes in the first diaphragm; (3) stacking conductive agent layers on the upper and lower sides of the first film, and hot pressing to obtain a composite film layer; (4) stacking current collector layers on the upper and lower sides of the composite membrane layer, and finally performing hot pressing.

9. The preparation method according to claim 8, characterized in that: Step (2) punches holes in the first membrane, and adds a lithium supplement into the resulting microporous structure.

10. The preparation method according to claim 8, characterized in that: Step (4) folds the composite film layer in a Z shape, stacks current collector layers on its upper and lower sides, and finally performs hot pressing.